Experience of remote customer service accessibility for adults with acquired speech disorders in the UK (Journal of Accessibility and Design for All, 2025)
Businesses and institutions have been increasing their reliance on telephone services over face-to-face interactions, and on automatic speech recognition over human operators. These trends risk disadvantaging people with speech conditions, whose speech is not easily understood. This qualitative study used semi-structured interviews to explore the experiences with customer services of people with acquired speech conditions. Thirteen people from the United Kingdom shared both positive and negative experiences of customer service accessibility, in relation to the use of technology, institutional practices, and interpersonal communication. Some of the main areas of challenge related to the lack of variety in communication channels, and barriers created within the existing ones due to time pressure and high communication demands on the customer, automatic speech recognition not meeting the needs of this population, and a lack of awareness of speech conditions among call centre staff, leading to negative assumptions. Participants shared key recommendations and positive experiences to have their needs met, including opportunity for multichannel communication, reducing time pressure on the customer, checking understanding, and companies keeping record of their communication needs.